Production of Porous Aluminium Using Sodium Chloride - Nová, Iva; Fraňa, Karel; Sobotka, Jiří; Solfronk, Pavel; Koreček, David; Nováková, Iva (Manufacturing Technology Journal, 2019)
Our workplace, Technical University of Liberec, is currently engaged in research and production of cellular metal systems. Basically, cellular metal systems are materials with lower density. It is a research in the field of mechanical engineering that is focused on the development of new materials. In general, many methods have been developed for the production of cellular metal systems, e.g. by BANHART [2] or ASHBY [4]. At their production, the direct gassing of molten metals (mostly aluminium ones) or gassing by the powder agents (e.g. specially formulated aluminium powders) are mostly used. Depending on the manufacturing method, a cellular system with open or closed cells can be obtained. The most commonly used metal is aluminium and its alloys. We are currently focusing on the production of porous aluminium by using sodium chloride. Sodium chloride occupies regular sites in the aluminium material and thus contributes to the aluminium porosity. After solidification of the aluminium, sodium chloride is dissolved in water. Sodium chloride is relatively inert to the aluminium and together with it, has a favourable density (2160 kgm-3) compared to the aluminium density (2700 kgm-3). The values of these physical quantities were observed on the produced aluminium test specimens having  60 x 10 mm: relative density of porous system REL; porosity of metal system P; amount of solid phase system volume fraction VPM; density of porous metal system PM and porous material Young's modulus of elasticity EPM.
Keywords: Metal System; Porous Metal System; Sodium Chloride; Casting; Aluminium Alloy